The Strategy of The Local Government of Bali Province in Handling Disaster due to The COVID-19 Pandemic - Kurniadi, Anwar; Bahar, Fauzi; Savitri, Aida Rahma (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The disaster because of the Covid-19 pandemic is a threat to national security that must be overcome. The Provincial Government of Bali has carried out various efforts including the involvement of traditional elements, but additional cases continue to occur. This study aims to analyze the implementation and obstacles on strategies of the Bali Provincial Government in disaster management because of the COVID-19 pandemic. This research used a qualitative descriptive study with a purposive sampling method. The results showed that: 1) The implementation of the strategy of the Bali Provincial Government involved all elements of pentahelix and also the involvement of the indigenous people in 1,493 Traditional Villages that an advantage of Bali Province in overcoming disasters because of the COVID-19 pandemic; 2) Obstacles in the implementing of the Covid-19 coping strategy occur in all elements of the strategy, as a result, the strategy being implemented is less than optimal. The conclusion in this study was the strategy of Bali the Local Government has implemented well but found many obstacles, especially in ceremonies (the differentiators) and business (economic tinking) that require the involvement of many people.